The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jcrs.2011.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Microincision versus small-incision coaxial cataract surgery using different power modes for hard nuclear cataract

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 19 publications
2
39
0
1
Order By: Relevance
“…[1][2][3] Likewise, microincision cataract surgery (MICS) can be achieved by sub-2 mm incisions. 4 The main advantages of MICS include minimising surgically induced astigmatism and reducing higher-order corneal aberrations. 5 When performing a combined phacovitrectomy (sequential phacoemulsification/intraocular lens (IOL) insertion followed by pars plana vitrectomy; PPPV), a smaller corneal wound size may have additional advantages to the subsequent vitrectomy, including avoiding the need for wound suturing and preventing the anterior chamber from collapsing during the subsequent PPPV.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Likewise, microincision cataract surgery (MICS) can be achieved by sub-2 mm incisions. 4 The main advantages of MICS include minimising surgically induced astigmatism and reducing higher-order corneal aberrations. 5 When performing a combined phacovitrectomy (sequential phacoemulsification/intraocular lens (IOL) insertion followed by pars plana vitrectomy; PPPV), a smaller corneal wound size may have additional advantages to the subsequent vitrectomy, including avoiding the need for wound suturing and preventing the anterior chamber from collapsing during the subsequent PPPV.…”
Section: Introductionmentioning
confidence: 99%
“…2 The intraoperative energy used and ocular damage can be decreased in MICS with the pulse and burst modes compared with the continuous mode for hard cataract. 3 Advanced phacoemulsification techniques may also decrease energy use. 4 The phaco-chop technique requires lower ultrasound (US) energy for nuclear management than the stop-and-chop technique in dense cataracts; however, it has been reported that the resulting endothelial loss was similar with both techniques in small-incision cataract surgery.…”
mentioning
confidence: 99%
“…11,12 CEC loss during cataract surgery can also occur as a result of several intraoperative factors, including toxic intraoperative medications, surgical corneal incisions, Descemet's membrane detachment, fluid turbulence inside the anterior chamber, total amount of ultrasound energy used, ultrasound energy dissipated close to the CEC, phacoemulsification parameters, free radicals, surgical complications such as posterior capsule rupture and vitreous loss that prolong surgery duration and manipulation, direct contact of surgical device on CEC and hard nucleus, anterior chamber collapse that leads to corneal deformity, IOL-related problems, inadequate surgical experience, and postoperative inflammation. 1,2,4,6,7,11,[13][14][15][16] In the present study, CEC loss in either group was assessed via cell density calculation on a specular microscope. Cell morphology secondary to CEC loss and central corneal thickness, which is not usually parallel, were not taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite all these facilities, corneal endothelial cell loss occurs due to various factors, with a loss rate between 6.9% and 42.6% reported in various studies. [1][2][3][4][5][6][7] Corneal transparency is maintained by the corneal endothelial cells, which serve as a physical barrier to the movement of fluid as well as an active pump across the cornea. The corneal endothelial cells are non-dividing cells developing a pumping activity that is crucial for corneal clarity and integrity.…”
Section: Introductionmentioning
confidence: 99%